Antibacterial Activity Test of Ethanol Extract of Sonneratia alba On Escherichia coli And Staphylococcus aureus - kevin wong; Jeane Mongi; Sonny D. Untu; Jabes W. Kanter; Hanna M. Rumagit; Nerni O. Potalangi (Biofarmasetikal Tropis (The Tropical Journal of Biopharmaceutical), 2025)
Antibacterial is a compound used to control the growth of harmful bacteria. Mangrove plants are strongly suspected to have bioactive content, the bioactive content contained in mangrove plants is useful in the pharmaceutical field as a medicinal ingredient. Sonneratia alba root contains secondary metabolite compounds Flavanoids, tannins and alkaloids that act as antibacterials. The purpose of this study was to determine the antibacterial activity of S.alba ethanol extract against Staphylococcus aureus bacteria and Escherichia coli bacteria. Extraction method by maceration, long extraction time 3 days. The extract obtained is then evaporated solvent in the rotary evaporator then the extract results are made concentrations of 25?g, 50?g, 100?g, and 150?g. antibacterial testing using the Kirby-Bauer method. The results showed that at concentrations of 25?g, 50?g, 100?g, and 150?g Sonneratia alba mangrove roots had antibacterial activity. But those that have strong antibacterial activity in Escherichia coli bacteria are at a concentration of 50? with while in Staphylococcus aureus bacteria are at a concentration of 150?g with an inhibitory zone of 18.6mm, and in Escherichia coli bacteria with an inhibitory zone of 18,3mm.